The Effect of the Minimum Wage at District/City on the Open Unemployment Rate in Java Before and During the Covid-19 Pandemic - Fahria Fahria (Jurusan Ilmu Ekonomi dan Studi Pembangunan Universitas Jenderal Soedirman, 2022)
This study aims to examine the effect of the minimum wage at the district/city level (MWD) on the open unemployment rate (OUR) before and during the Covid-19 pandemic on Java Island. In addition, this study also wants to see the impacts of other variables, namely the Human Development Index (HDI), Gross Regional Domestic Product (GRDP), and Labor Force Participation Rate (LFPR) on the OUR. This study applied a Geographically Weighted Regression (GWR) to data of all districts/cities in Java Island in 2019 and 2020. The results showed that before the Covid-19 pandemic, the change in MWD had a significant effect on OUR in 44 districts/cities, but during the pandemic, it affected OUR in 64 districts/cities. The estimated parameter coefficient for MWD is higher during the pandemic. Areas whose MWD coefficient is higher than before the pandemic are South Tangerang, Tangerang City, Serang city, Serang district, all DIY areas, all districts/cities in Central Java, and some areas in East Java. This study also found that the impacts of HDI, GRDP, and LFPR on OUR vary spacially before and during the Covid-19 pandemic.